2012
DOI: 10.1016/j.ijpara.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of apicomplexan secretory organelles

Abstract: The alveolate superphylum includes many free-living and parasitic organisms, which are united by the presence of alveolar sacs lying proximal to the plasma membrane, providing cell structure. All species comprising the apicomplexan group of alveolates are parasites and have adapted to the unique requirements of the parasitic lifestyle. Here the evolution of apicomplexan secretory organelles that are involved in the critical process of egress from one cell and invasion of another is explored. The variations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 126 publications
1
96
0
4
Order By: Relevance
“…Genetic tractability and easy visualization by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 microscopy make Toxoplasma a well-used model for many general studies of apicomplexan cell biology. In the animal host, extracellular Toxoplasma parasites extend and retract the conoid through the apical polar ring, a process thought to contribute mechanically to the process of host cell invasion (Gubbels and Duraisingh 2012). Recently, it has been observed that following duplication of the parasite centrosome, which is associated with the nucleus, a fibrous connection extends from the duplicated centrosome to the apical polar ring providing a hard-wired link that helps orchestrate daughter cell budding.…”
Section: (B) Apicomplexan Parasitesmentioning
confidence: 99%
“…Genetic tractability and easy visualization by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 microscopy make Toxoplasma a well-used model for many general studies of apicomplexan cell biology. In the animal host, extracellular Toxoplasma parasites extend and retract the conoid through the apical polar ring, a process thought to contribute mechanically to the process of host cell invasion (Gubbels and Duraisingh 2012). Recently, it has been observed that following duplication of the parasite centrosome, which is associated with the nucleus, a fibrous connection extends from the duplicated centrosome to the apical polar ring providing a hard-wired link that helps orchestrate daughter cell budding.…”
Section: (B) Apicomplexan Parasitesmentioning
confidence: 99%
“…This process, termed schizogony, involves an unusual membrane-cytoskeletal complex known as the Inner Membrane Complex. The IMC is derived from cortical alveolae [35,36] -- a morphological character defining the superphylum Alveolata, including apicomplexans, chromerids and colpodellids, ciliates, and dinoflagellates [7] (Fig 2). …”
Section: Imc: Homology With Ciliate and Dinoflagellate Alveolaementioning
confidence: 99%
“…Ciliate alveolae are specialized for storage and regulatory activities [35], while dinoflagellate alveolae have evolved into the armored plates characteristic of this phylum [36]. In the apicomplexa, the IMC forms a patchwork of Golgi-derived flattened membrane vesicles, closely apposed to the plasma membrane to yield a triple membrane [37,38].…”
Section: Imc: Homology With Ciliate and Dinoflagellate Alveolaementioning
confidence: 99%
See 1 more Smart Citation
“…This same principle, of finding homologies and making comparisons, can also be applied to other organelles, with interesting work now showing functional insight between endolysosomes and the secretory granules of ecologically important organisms like ciliates (Elde et al 2005) and dinoflagellates (Gubbels and Duraisingh 2012) and medically important organisms like the malaria parasite Plasmodium spp. or the related parasite T. gondii (Gubbels and Duraisingh 2012;Klinger et al 2013). Finally, the clear structural relationships that have emerged for the paralogous Rab and SNARE families, and which provided some of the impetus for the OPH, have clearly been of great utility.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%